The proline-rich antimicrobial peptide Api137 disrupts large ribosomal subunit assembly and induces misfolding - Simon Malte Lauer; Jakob Gasse; Andor Krizsan; Maren Reepmeyer; Thiemo Sprink; Rainer Nikolay; Christian M. T. Spahn; Ralf Hoffmann (Nature Communications)
Abstract The proline-rich antimicrobial designer peptide Api137 inhibits protein expression in bacteria by binding simultaneously to the ribosomal polypeptide exit tunnel and the release factor (RF), depleting the cellular RF pool and leading to ribosomal arrest at stop codons. This study investigates the additional effect of Api137 on the assembly of ribosomes using an Escherichia coli reporter strain expressing one ribosomal protein per 30S and 50S subunit tagged with mCherry and EGFP, respectively. Separation of cellular extracts derived from cells exposed to Api137 in a sucrose gradient reveals elevated levels of partially assembled and not fully matured precursors of the 50S subunit (pre-50S). High-resolution structures obtained by cryogenic electron microscopy demonstrate that a large proportion of pre-50S states are missing up to five proteins (uL22, bL32, uL29, bL23, and uL16) and have misfolded helices in 23S rRNA domain IV. These data suggest a second mechanism for Api137, wherein it disrupts 50S subunit assembly by inducing the formation of misfolded precursor particles potentially incapable of evolving into active ribosomes, suggesting a bactericidal mechanism.